Effect of Teachers’ Organizational Skills on Their Academic Optimism - Muhammad Shahroze Siddiqui; Dr. Wajiha Kanwal; Khalida Parveen; Iffat Shaheen; Nosheen Wajid (Journal of Management Practices, Humanities and Social Sciences, 2022)
The study was conducted to determine the effect of three organizational skills (lesson planning, communication, and time management) of teachers on their academic optimism, which is defined as “integration of teacher self-efficacy, academic press, and trust in parents and students.” Population of the study was elementary school teachers ESTs of public schools of district Rawalpindi Pakistan. Sample size was 150, and convenient sampling technique was used to gather data from Elementary school teachers. The nature of this research was descriptive and quantitative and based on quantitative research to find the effect of organizational skills of teachers on their academic optimism. Design of this quantitative research is predictive correlation. Dependent and independent variables were measured through a questionnaire. Research tool was questionnaire. Teachers’ organizational skills were measured through a self-developed questionnaire, while Teacher Academic Optimism Scale Elementary (TAOS-E) by Hoy (2001) was used to measure level of optimism. Data was collected through survey and then analyzed using SPSS software to see the quantified result among variables. This study revealed moderate correlation between organizational skills and academic optimism. The regression analysis revealed that there are 32 percent changes. It is suggested that there should be proper in service and pre-service teacher training programs for polishing the organizational skills of teacher, which definitely will improve teaching-learning process. Universities should conduct more research on the factors of academic optimism of teachers. Ways should be identified for improvement of academic optimism levels.